ETNOBOTANI TUMBUHAN OBAT DI DESA PATEMON KECAMATAN TENGARAN KABUPATEN SEMARANG - Jaya, Surachman; Suprihati, Suprihati (Agros Journal of Agriculture Science, 2024)
Ethnobotany is a branch of science that studies how people use plants. Patemon Village has abundant biodiversity potential for medicinal plants. Therefore, research on the ethnobotany of medicinal plants in Patemon Village was conducted. The descriptive qualitative narrative method was used in this study with 10 respondents from 4 hamlets in Patemon Village, namely Wates Kulon, Surodadi, Bontit Hamlets representing areas bordering the natural forest area of Mount Merbabu and Patemon Hamlet as the center of government. Respondent sampling used snowball sampling. Interviews were conducted with 10 key informants (4 hamlet heads, 6 shamans/healers/community leaders) and supporting informants of 5 medicinal plant farmers with the highest Relative Frequency of Citation (RFC) and data analysis using simple statistics. The results of the study showed that the types of medicinal plants used by the Patemon Village community were 40 types, consisting of 21 families, including ginger (RFC 1), lemongrass (0.9), and turmeric (0.8) which were used for the treatment and prevention of diseases, mostly used to treat internal diseases. The part of the medicinal plant most widely used for treatment is the leaves, which is 35%. 48% of medicinal plants are used by drinking them. Plants that are used as medicine are obtained from home gardens with a value of 85%. To increase the yield of ginger plants, ginger farmers in Patemon produce their own ginger seeds, this is done because farmers can choose seeds with good quality.